Notes and observations on courtship and mating in Tityus (Atreus) magnimanus Pocock, 1897 (Scorpiones: Buthidae) - LK Ross (Journal of Venomous Animals and Toxins including Tropical Diseases, 2009)
Courtship and mating behaviors of the scorpion Tityus (Atreus) magnimanus are herein described, consisting of various components that pertain to four distinct behavioral stages. The courtship and mating rituals of Tityus (Atreus) magnimanus are similar to those of other scorpions. Behavioral components are presented in an ethogram to demonstrate their occurrence during mating sequences. The current report is presented as observational data that were acquired during life history studies of this species.